LEVERAGE DAN PROFITABILITAS DALAM MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN HEALTHCARE YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE 2019-2022 DENGAN MODERASI VARIABEL KEBIJAKAN DIVIDEN - Labiba, Ines; Subaida, Ida; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
This research is motivated by the unstable economic conditions due to the impact of Covid-19. The Covid-19 pandemic has increased enormous economic uncertainty. This is the main cause of the decline in investor confidence which gives an impact on the fall in the volume of investments. This uncertainty and decline in confidence affects the profits of most corporate sectors in the Indonesia Stock Exchange. In contrast to other sectors, health products from Healthcare companies are much needed by the society. Whether companies in the Healthcare sector also experience the same thing as companies in other sectors which endure a decline in share prices and investment levels while the level of consumption of health products is increasing. The aim of this research is to examine the effect of leverage and profitability on share prices with dividend policy as a moderating variable. The population in this study are Healthcare companies listed on the Indonesia Stock Exchange for 2019-2022 period. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this research used the structural equation modeling- Smart Partial Least Square (SmartPLS). The results of hypothesis testing using SmartPLS 3.0 showed that leverage had a significant positive effect on share prices, profitability had a significant positive effect on share prices, dividend policy strengthened the influence of leverage on share prices and dividend policy weakened the influence of profitability on share prices.